2001
DOI: 10.1007/s11920-001-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of panic disorder

Abstract: Of the anxiety disorders, panic disorder (PD) has been the most extensively studied from a genetic standpoint. Results of family studies have consistently demonstrated that PD runs in families, and twin studies indicate that genes contribute to this familiality. However, phenotypic and genetic complexity has made finding the specific genes involved in PD a challenge. There is still uncertainty about how best to define the phenotype for genetic studies and whether it is the clinical phenotype of PD or more late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…These findings corroborate those from prior family studies of clinical and community samples of probands for all disorders including substance use disorders [4,12,20], the schizophrenias [10,18,28], affective disorders [2,3,14,19,23,[25][26][27], and anxiety disorders [6,11]. We also found that there was strong specificity of familial aggregation of the probands' disorders, particularly in parents and siblings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings corroborate those from prior family studies of clinical and community samples of probands for all disorders including substance use disorders [4,12,20], the schizophrenias [10,18,28], affective disorders [2,3,14,19,23,[25][26][27], and anxiety disorders [6,11]. We also found that there was strong specificity of familial aggregation of the probands' disorders, particularly in parents and siblings.…”
Section: Discussionsupporting
confidence: 90%
“…From less extended research it is also clear that among the anxiety disorders, panic disorders, agoraphobia, and generalized anxiety disorders are recurrent in families [6,11]. There is also evidence of a familial risk of suicidal ideation and suicidal behaviour in the general population [9].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Estimates from family and twin studies ascribe a genetic contribution of approximately 40% to the disease etiology of the disorder. [5][6][7][8] However, the mechanism underlying PD is still unknown and presumably involves numerous susceptibility genes with major and/or minor effects. 9,10 Furthermore, the possibility of allelic heterogeneity, which most likely will reduce the power of performed studies to detect associated genes, exists.…”
Section: Introductionmentioning
confidence: 99%
“…First-degree relatives are more liable to develop PD than the general population. [8][9][10][11] The majority of this familial risk is thought to be conferred by genetic factors. Twin studies have strengthened the case for genes, rather than for common family environments, in predicting PD, as evidenced by the higher concordance in monozygotic twins vs. dizygotic twins.…”
Section: Pathogenesis Of Panic Disordermentioning
confidence: 99%